ACCELERATING IMPACTS OF CGIAR CLIMATE RESEARCH FOR AFRICA (AICCRA) (P173398) UPDATED ENVIRONMENTAL AND SOCIAL MANAGEMENT PLAN (ESMP) - International Livestock Research Institute; Alliance of Bioversity International and CIAT; International Crop Research for Semi-Arid Tropics (2023)
The Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project activities in Kenya are focused on improving the quality of Climate Smart Agricultural (CSA) practices and information services in the Arid and Semi-Arid Land (ASAL) areas of Kenya. The project seeks to increase awareness and uptake of selected climate-smart agricultural (CSA) practices and improve access to Climate Information Services (CIS), especially by women and the youth. AICCRA-Kenya is also focused on piloting CSA innovations and CIS technologies in farmers’ fields to expand the awareness and application of relevant climate adaption innovations among farmers. In line with this plan, the Alliance of the Bioversity International and CIAT (Alliance) is collaborating with the Africa Conservation Tillage Network (ACTN) and the universities of Murang’a, Chuka, and Taita Taveta to scale out the uptake of validated CSA and CIS and strengthen the resilience of Kenya dryland agriculture and food systems. The International Crop Research Institute for Semi-Arid Tropics (ICRISAT) is also scheduled to carries out similar CSA demonstrations on farmer fields whilst the International Livestock Research Institute (ILRI) intends to introduce climate smart pastoralism to pastoralists. As envisaged, the pilot of CSA innovations and CIS technologies on farmers’ fields is expected to lead to some environmental and social risks at the proposed sites for demonstrations. In line with this expectation and following the requirements of the project’s Environmental and Social Risk Management (ESRM) guide, the Alliance conducted site-specific screening of farm plots identified for CSA demonstrations.